ChemInform Abstract: Efficient Method for Demethylation of Aryl Methyl Ether Using Aliquat‐336. Issue 7 (18th February 2014) - Waghmode, Suresh B.; Mahale, Ganesh; Patil, Viraj P.; Renalson, Kartik; Singh, Dharmendra
Abstract A rapid and selective method for the title reaction is applied to a wide range of substrates.